Changes in behavior and fatty acid composition induced by long-term reduction in murine Δ6-desaturation activity. (April 2020) - Harauma, Akiko; Sueyasu, Toshiaki; Tokuda, Hisanori; Yasuda, Hidemi; Hoshi, Yukino; Kaneda, Yoshihisa; Rogi, Tomohiro; Shibata, Hiroshi; Nakamura, Manabu T.; Moriguchi, Toru
Highlights: Δ6 desaturase heterozygous mice would be useful for investigating the effect of reduced fatty acid synthesis over the long term. Brain and liver of ARA were decreased in the heterozygous mice during the growth-maturity period. Whereas DHA were decreased in the liver only in the old age period in the heterozygous mice. For newborns, and humans in minor alleles with low lipid metabolism, direct ARA intake is important during the growth-maturity period. Abstract: Polyunsaturated fatty acids (PUFAs), especially arachidonic acid (ARA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), play an important role in biological regulation. In our previous study using mice deficient in Δ6 desaturase (D6D), we reported that ARA is required for body growth, while DHA is necessary for functional development. In mammals, ARA and DHA are supplied directly or by synthesis from linoleic acid (LA) and α-linolenic acid (ALA). However, as desaturase enzyme activity is immature or low in newborns, and humans with minor alleles of the gene encoding desaturase, respectively, they require dietary supplementation with ARA and DHA. To investigate how the body reacts to a long-term reduction in fatty acid synthesis, we measured behavioral changes and fatty acid composition in mice heterozygous for the D6D null mutation with reduced D6D activity fed a diet containing only LA and ALA as PUFAs. During the growth-maturity period, heterozygous mice showed a slightly change in interest and curiosity compared with the wild-type group. ARA levels were decreased in the brain and liver in the heterozygous group, especially during the growth-maturity period, whereas DHA levels were decreased in the liver only in the old age period, suggesting that there are differences in the synthesis of and demand for ARA and DHA during life. For newborns, and humans with minor alleles with low desaturase activity, direct ARA intake is particularly important during the growth-maturity period, but they may need to be supplemented with DHA in the old age period. Further research is needed to determine the optimal intake and duration of these fatty acids.